2000
DOI: 10.4269/ajtmh.2000.62.341
|View full text |Cite
|
Sign up to set email alerts
|

Invasive bacterial infections of children in a rural province in the central Philippines.

Abstract: Abstract. The etiology of invasive bacterial infections was studied among 956 Filipino children less than five years old who fulfilled the World Health Organization criteria for severe or very severe pneumonia or had suspected meningitis or sepsis. The most common invasive infections were due to Streptococcus pneumoniae (12 [1.3%]) and Haemophilus influenzae (12 [1.3%]); including four cases of pneumococcal meningitis and 11 cases of H. influenzae meningitis. Type 1 was the most common (six of the 12 isolates)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…The prevalence of H. influenzae carriage in HIV-infected children was reported for India (24%) [70] and Zambia (29%) [71], two lower-middle income countries. The prevalence of H. influenzae carriage in ill children from three lower-middle income countries ranged between 15.2% and 53.5% [36], [61], [62]. PCR generally yielded higher rates of H. influenzae carriage than microbiology in both healthy (31.4%–70% vs. 1.1%–28.6%) and ill (50%–53.5% vs. 15.2%–36.6%) subjects.…”
Section: Resultsmentioning
confidence: 95%
“…The prevalence of H. influenzae carriage in HIV-infected children was reported for India (24%) [70] and Zambia (29%) [71], two lower-middle income countries. The prevalence of H. influenzae carriage in ill children from three lower-middle income countries ranged between 15.2% and 53.5% [36], [61], [62]. PCR generally yielded higher rates of H. influenzae carriage than microbiology in both healthy (31.4%–70% vs. 1.1%–28.6%) and ill (50%–53.5% vs. 15.2%–36.6%) subjects.…”
Section: Resultsmentioning
confidence: 95%
“…6 Studies involving bacterial culture from blood have found that Streptococcus pneumoniae and Haemophilus influenzae are the most common etiological agents for pneumonia and meningitis in children with the pneumococcal serotypes 1, 6, 9, 14, 19, 23 and H. influenzae serotype b as the most prevalent causative agents. 7,8 Although official data on Hib disease in the Philippines is limited, studies have reported that the majority (∼80%) of Hib-related pneumonia and meningitis occur in the first year of life. 9,10 In view of the high global coverage of combined DTP vaccines, the addition of new antigens to existing DTP vaccines is the most effective way to achieve rapid vaccine coverage with the new antigen.…”
Section: Resultsmentioning
confidence: 99%
“…Antimicrobial susceptibility tests were performed as previously reported. 27,28 Radiological investigation Postero-anterior and lateral chest radiographs were obtained for most infants and read by the study radiologist, blinded to clinical information, and classified for the presence and type of infiltrates. A dense infiltrate was defined as fluffy opacities with ill-defined margins, with lobar, segmental or patchy distribution.…”
Section: Laboratory Methodsmentioning
confidence: 99%
“…27,28 The study was approved by the Institutional Review Board of the Research Institute for Tropical Medicine. As part of a large prospective study on serious infections in children under 5 years of age, infants below 2 months were enrolled using criteria, partly based on the WHO case management protocol for Acute Respiratory Infections, 29 or our definitions, 28 if they had: (1) clinically defined severe pneumonia (cough or difficult breathing and respiratory rate X60/min or severe lower chest wall indrawing), 29 (2) suspected meningitis indicated by convulsions, abnormal sleepiness or difficulty in waking, or neurologic abnormalities 28 or (3) clinical suspicion of sepsis (any of the following: fever >38.01C or hypothermia <36.01C, poor feeding, distended and tense abdomen, apneic episodes, grunting, central cyanosis and jaundice).…”
Section: Study Design and Patient Enrollmentmentioning
confidence: 99%
See 1 more Smart Citation